OPPORTUNITIES FOR POLYTECHNIC GRADUATES TO BECOME ENTREPRENEURS IN THE AUTOMOTIVE SECTOR DURING THE COVID-19 PANDEMIC - Yusron, Willi Nur; Noor, Ridwan Adam M.; Mubarak, Ibnu; Nurhadi, Idham (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2021)
The purpose of this study was to determine the entrepreneurial opportunities in the automotive sector during the pandemic. This study uses a survey method with a population of graduates of the Mechanical Engineering KBK Automotive D3 Study Program at a university located in the city of Bandung, West Java. The type of data in this study is mainly based on the responses of respondents who were collected through a questionnaire made in the google form. Based on the results of the study, it was found that the entrepreneurial opportunities in the automotive sector during the pandemic were the most chosen by the respondents in the first place, selling spare parts and service in second. This opportunity was obtained from the experience of those who worked in the automotive sector in 2020 which occurred during the covid-19 pandemic.